Respuesta :

Step-by-step explanation:

1)

x⁴×x^a = x¹²

you know that you can add the exponents when multiplying terms with the same base value/variable ?

because that is what we are doing here to solve it :

x^(4 + a) = x¹²

therefore,

4 + a = 12

a = 8

2)

y^b / y⁵ = y²

similar to 1), but when we divide, we subtract the exponents.

y^(b - 5) = y²

b - 5 = 2

b = 7

3)

3^c = 1/27

27 = 3³

27×3^c = 1

3³×3^c = 1

3^(3 + c) = 1

now we need to remember : x⁰ = 1.

therefore, 3⁰ = 1

3^(3 + c) = 3⁰

3 + c = 0

c = -3

4)

(m³)² = m^d

aha !

now we need to remember, we can multiply the exponents, when we have an exponent of an exponent term.

m^(3×2) = m^d

3×2 = d

6 = d

5)

7⁰ = e

remember, x⁰ = 1, so also 7⁰ = 1.

therefore, e = 1.

6)

4^-2 × 4⁹ × 4^‐5 = 4^f

so, now we need apply what we just learned to a sequence of operations :

each term has the same base value (4), and they are all multiplied, so we can do the described adding of the exponents :

4^(-2 + 9 - 5) = 4^f

therefore,

f = -2 + 9 - 5 = 2

Answer:

just here 4 points

Step-by-step explanation: